Look before you leap: the effects of cognitive impulsiveness and reasoning process on rational decision making - Jelihovschi, Ana Paula Gomes (2016)
Impulsivity may lead to several unfortunate consequences and maladaptive behaviors for clinical and non-clinical people. Although many studies discuss the negative impact of it, few of them emphasize the relationship between cognitive impulsiveness and decision making in non-clinical subjects. The aim of this study is to investigate the effects of cognitive impulsiveness on decision making and explore the strategies used by participants to solve problems. For this purpose, we apply two measures of impulsivity: the self-report Barratt Impulsiveness Scale (BIS-11) and the performance based Cognitive Reflection Test (CRT).This is the first study that compares self-report impulsiveness based on BIS-11 and performance-based reflectivity measured by CRT. Moreover, due to the fact that we apply the instruments on pen and paper, it is possible to evaluate participants’ reasoning processes employed to answer CRT questions. These reasoning processes are related to the role of Executive Functions for decision making and its relationship with impulsiveness. In practical terms, we observed participants’ strategies by analyzing their calculation expressions and data organization to answer CRT questions in the paper sheet. The sample consists of 191 non-clinical adults, professionals, and undergraduate students from the fields of business, management, and accounting. Results show that cognitive impulsiveness may negatively affect performance. Moreover, there is no difference in strategies used by impulsive and non-impulsive people during a decision making, and who calculate in the paper sheet perform better. Finally, people who inhibit their immediate answers also perform better during a decision making.